Extending the Newns-Anderson model to allow nanotransport studies through molecules with floppy degrees of freedom - Bâldea, Ioan (epl, 2012)
The Newns-Anderson model is ubiquitous in studies of the molecular transport in the presence of solvent (outer) reorganization. The present work demonstrates that intramolecular reorganization can also be significant for the transport through molecules with floppy degrees of freedom, for which the Newns-Anderson model can be extended. The expressions of the model parameters deduced from electronic structure calculations for (4, 4')-bipyridine (44BPY) quantitatively differ from those characteristic for outer reorganization due to strong intramolecular anharmonicities. These expressions can be utilized as input in transport calculations for 44BPY-based molecular junctions of experimental interest (Xu B. and Tao N. J., Science [http://dx.doi.org/10.1126/science.1087481] , 301 (2003) 1221 ; Pobelov I. V. et al. , J. Am. Chem. Soc. [http://dx.doi.org/10.1021/ja8054194] , 130 (2008) 16045 ; Widawsky J. R. et al. , Nano Lett. [http://dx.doi.org/10.1021/nl203634m] , 12 (2012) 354 ).